Reduced magnetization curves of Ising nanoparticles with high critical temperature. (2nd April 2020) - Kaneyoshi, T.
ABSTRACT: The magnetic properties (phase diagram, the thermal variations of magnetization and the reduced magnetization curve) in graphene-like Ising nanoparticles are examined by the effective-field theory with correlations. The effects of surface exchange interaction JS on the magnetic properties are discussed. When JS is larger than the critical value JSC, a nanoparticle with high critical temperature is possible. The value of JSC depends on the shape and the degree of structural packing of the nanoparticle. It is found that there exist two types of reduced magnetization curves for a nanoparticle with JS  >  JSC .